A Reconstruction of Justice in Natural Resource Governance Based on the Rights of Nature: The Restitution of the UNESA Reservoir in Surabaya - Berliana Ayu Kusumawardani; Abdul Aziz Nasihudin; Sri Wahyu Handayani (Greenation International Journal of Law and Social Sciences, 2026)
The control of natural resources within the Indonesian legal system to date continues to reflect the dominance of an anthropocentric paradigm, positioning nature primarily as an object of exploitation. Consequently, the conception of justice that emerges remains largely confined to the distributional dimension of benefits for human interests. This condition has resulted in inadequate protection of ecological functions and the failure to realize substantive justice encompassing environmental sustainability. This study aims to analyze the construction of justice in the control of natural resources, to examine the concept of the Rights of Nature from the perspective of natural philosophy and its relevance to legal reform, and to formulate a model for reconstructing justice based on the Rights of Nature in the case of the restitution of the UNESA Reservoir in Surabaya. The research employs a normative legal method, utilizing conceptual, statutory, and case-based approaches. The findings indicate that justice in the control of natural resources has not fully integrated the ecological dimension, whereas the Rights of Nature concept provides a foundational basis for expanding the meaning of justice through the recognition of the intrinsic value of nature. The reconstruction of justice is carried out through the strengthening of normative, institutional, and governance aspects, positioning ecosystem sustainability as an integral component of justice itself.